2020
DOI: 10.1093/ajcn/nqz331
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the proportion of fat-free mass loss during weight loss, changes in appetite, and subsequent weight change: results from a randomized 2-stage dietary intervention trial

Abstract: Background Dynamic changes in body composition which occur during weight loss may have an influential role on subsequent energy balance behaviors and weight. Objectives The aim of this article is to consider the effect of proportionate changes in body composition during weight loss on subsequent changes in appetite and weight outcomes at 26 wk in individuals engaged in a weight loss maintenance intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 45 publications
(71 reference statements)
3
31
2
Order By: Relevance
“…124,125 A nonleptin system (and so far unidentified adipostatic signals) has recently been implicated in the compensatory hypophagia that plays a critical role in the recovery from rapid weight gain induced by overfeeding. 126 On the other hand, the notion of a feedback loop between FFM deficit and compensatory hyperphagia (Figure 9), as suggested by the MSE reanalysis 63 and by recent studies of weight regain after caloric restriction in humans [98][99][100][101][102] and in mice, 127…”
Section: Adipostats and Proteinstats Awaiting Discoverymentioning
confidence: 93%
See 2 more Smart Citations
“…124,125 A nonleptin system (and so far unidentified adipostatic signals) has recently been implicated in the compensatory hypophagia that plays a critical role in the recovery from rapid weight gain induced by overfeeding. 126 On the other hand, the notion of a feedback loop between FFM deficit and compensatory hyperphagia (Figure 9), as suggested by the MSE reanalysis 63 and by recent studies of weight regain after caloric restriction in humans [98][99][100][101][102] and in mice, 127…”
Section: Adipostats and Proteinstats Awaiting Discoverymentioning
confidence: 93%
“…Specifically in their reanalysis of the DiOGenes study, they showed that the fraction of weight loss as FFM in men was positively associated with weight regain and with increased appetitive factors such as hunger and desire to eat. 101 Finally, the recent report 102 that following a 12-week aerobic exercise intervention aimed at weight loss in young adults with overweight/obesity, those who lost the greatest amount of FFM showed that the highest increase in reward-driven feeding (which is a strong predictor of energy intake) provides further support for the notion that FFM deficit drives food intake. Consequently, a role for lean tissue depletion driving hyperphagia has direct repercussions for obesity management, as it suggests that various strategies (dietary, behavioral, or pharmacologic) that reduce the loss of lean tissue are also likely to reduce the drive for hunger and thus improve the efficacy of dietary weight loss interventions.…”
Section: Management Of Obesity and Cachexiamentioning
confidence: 97%
See 1 more Smart Citation
“…To assess whether changes in BC occurring during WL were asso- hunger and desire to eat were observed in the male group, suggesting a potentially functional role of dynamic changes in BC in EB regulation. 142 The evidence from the CALERIE studies shows similarly weak evidence of small alterations in appetitive states. 86,91,92,124 These studies provide limited evidence under conservative conditions (10% WL in people with a high body weight and FM) that the relationship between changes in BC and appetitive outcomes so clearly elucidated in the Minnesota study 141,143 are (barely) detectable, but small, at lower levels of WL in people with a higher FM than the Minnesota or CNL subjects.…”
Section: Evidence For Changes In Functional Body Composition Influementioning
confidence: 97%
“…As body weight is reduced, so too is there a reduction of both fat mass (FM) and FFM, which is associated with an increased drive to eat (4). This may contribute to weight regain after periods of intentional or unintentional starvation, with FFM playing a central role (5,6). While the biological link between FFM loss and elevated hunger remains controversial, current best practice suggests preserving muscle mass as patients with obesity lose weight (7).…”
Section: Introductionmentioning
confidence: 99%